Upaya Pencegahan Peredaran Narkoba di Kelurahan Sambinae - Nike Ardiansyah (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2024)
This study aims to describe the strategies for preventing drug circulation in Sambinae Village, Bima City, using a qualitative descriptive method. The research was conducted through in-depth interviews, participatory observation, and documentation over one month, from May 20 to June 20, 2024. The main focus of this study is to explore inter-agency coordination, resource allocation, and the strengthening of laws and regulations in drug prevention efforts. The findings indicate that Sambinae Village has successfully established effective coordination between agencies such as Bhabinkamtibmas, Babinsa, religious leaders, and community leaders, with support from the National Narcotics Agency (BNN). This coordination has resulted in a strong synergy in efforts to create a drug-free environment. Additionally, the prevention strategies implemented focus on all levels of society using Soft Power, Hard Power, and Smart Power approaches, where Soft Power emphasizes outreach and education, Hard Power involves strict law enforcement, and Smart Power integrates technology into monitoring and education. However, the study also reveals challenges such as a lack of rehabilitation facilities and low community participation. It was found that the community tends to be passive in supporting drug prevention programs, although awareness of the dangers of drugs has increased. In conclusion, despite significant efforts by the village in drug prevention, there is still a need for improvements in resource support, cross-sector coordination, and community participation to achieve more optimal results.